Unleashing Excellence: Integrated Facility Management, Organizational Communication, and Education Service Quality - Mentari, Sarita; Prasetyo, Muhammad Anggung Manumanoso (UII Darullughah Waddawah Pasuruan, 2024)
The study aims to examine the influence of facility management and organizational communication on the quality of educational services using a quantitative research method with a survey approach. The sample size consists of 35 respondents. Data collection was conducted through questionnaires, and multiple regression analysis was employed for data analysis. The results indicate a significant positive effect of facility management on the quality of educational services (T-statistic = 2.779, p < 0.05). Similarly, organizational communication was found to have a significant positive impact on service quality (T-statistic = 3.582, p < 0.05). Furthermore, the combined effect of facility management and organizational communication on the quality of educational services was found to be significant (F-value = 8.850, p < 0.05). These findings highlight the importance of facilities and infrastructure in delivering quality services and emphasize the crucial role of effective communication in service implementation. The study suggests that institutional managers should prioritize the enhancement of facilities and infrastructure as a policy priority and consider effective communication skills as a prerequisite for recruiting professional educators.